Design Methods for Business Information Systems on WEB 2.0 and Cloud Computing Basis - Kisimov, Valentin; Velev, Dimitar (Research Papers, 2009)
The paper proposes methods for designing business information systems on the basis of the most actual and sophisticated at the present moment information technologies – Web 2.0 and Cloud Computing. The purpose, essence, architectural components and the characteristics of those two technologies are presented with a special emphasis on their application in the design of business information systems. The requirements to the software needed for the design of business information systems are defined. Methods for designing business information systems are proposed correspondingly on the basis of Web 2.0 (Design methods through different patterns – SOA, SaaS, Participation – Mutual activity, Mashup, Synchronized Web, Structured Information, User multifunctionality) and Cloud Computing (Design methods for Network as a Service, Computing as a Service, Application as a Service).